Fresh Herbage for Dairy Cattle
DOI: 10.1007/978-1-4020-5452-5_1
|View full text |Cite
|
Sign up to set email alerts
|

Achieving High Dry-Matter Intake From Pasture With Grazing Dairy Cows

Abstract: Abstract. Due to economic, environmental and animal-welfare constraints, it is envisaged that in the future a larger proportion of the milk produced in temperate regions will be produced from grazed pasture. However, with the selection of modern higher-production dairy cows, increased emphasis on product quality and issues associated with nitrogen leaching, soil compaction, greenhouse-gas emissions and animal welfare, pasture-based systems will also require higher per-animal productivity in the future. This wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
1
3

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 69 publications
(64 reference statements)
4
69
1
3
Order By: Relevance
“…The actual reduction in milk production observed (1.1 kg milk/2.5 UFL 5 0.44 kg) is similar to that associated with a 1-kg reduction in daily herbage allowance (Peyraud et al, 2001). While it is widely acknowledged that milk production from pasture is dependent on numerous environmental, plant, animal and management factors controlling herbage intake and rumen digestion (Dillon, 2006), the results of this analysis illustrate that as SR increases by one cow/ha, the net energetic consequences are akin to a reduction of 1 kg in daily herbage allowance per cow. Holmes et al (2002) suggested that cows per ha is increasingly misleading as a measure of the balance between feed demand and supply, although cows per ha is still widely used.…”
Section: Discussionmentioning
confidence: 94%
“…The actual reduction in milk production observed (1.1 kg milk/2.5 UFL 5 0.44 kg) is similar to that associated with a 1-kg reduction in daily herbage allowance (Peyraud et al, 2001). While it is widely acknowledged that milk production from pasture is dependent on numerous environmental, plant, animal and management factors controlling herbage intake and rumen digestion (Dillon, 2006), the results of this analysis illustrate that as SR increases by one cow/ha, the net energetic consequences are akin to a reduction of 1 kg in daily herbage allowance per cow. Holmes et al (2002) suggested that cows per ha is increasingly misleading as a measure of the balance between feed demand and supply, although cows per ha is still widely used.…”
Section: Discussionmentioning
confidence: 94%
“…However, the biological efficiency of supplementation can vary widely as it can be affected by several co-varying factors, including the level of pasture allowance and pasture intake, and the type and amount of supplementation (Dillon, 2006). Grazing cows fed starch-or silage-based supplements are known to achieve satiety sooner, thus reaching faster cessation of grazing with concurrent decreases in pasture intake (Hills et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Grazing cows fed starch-or silage-based supplements are known to achieve satiety sooner, thus reaching faster cessation of grazing with concurrent decreases in pasture intake (Hills et al, 2015). Consequently, the resulting substitution rate, or decrease of pasture intake per kilogram of supplement, could reduce the marginal milk response per kilogram of supplementation (Bargo et al, 2002;Dillon, 2006). As a general rule, greater milk response to supplementation is obtained in high stocking rate (HSR) systems because conditions that are necessary to minimize pasture substitution (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…There has been renewed international interest in grazing production systems (Macdonald et al 2008a) as a result of (i) reductions in milk prices in many countries, (ii) increments in production costs (Dillon et al 2005) and (iii) perceived environmental and animal welfare concerns associated with intensive dairying (Dillon 2006). This interest has triggered further studies on stocking rate (SR)*a topic extensively studied in countries with pasturebased dairy systems since the 1960s.…”
Section: Introductionmentioning
confidence: 99%
“…Herbage intake at grazing Intake of herbage has been identified as the main factor limiting milk yield of grazing cows (Leaver 1985;Dillon 2006). HI is affected by environmental factors such as rainfall and temperature, pasture characteristics such as herbage mass and structure, sward species, herbage quality Dillon 2006), and cow characteristics including genetic potential for milk yield (Horan et al 2006), stage of lactation (Stockdale et al 1987), LW and parity (Peyraud et al 1996).…”
Section: Introductionmentioning
confidence: 99%